Environmental dimensionality simplifies biological predictability under complex global change - Peixuan Liu; Bin Huang; Yuan Jia; Junyan Li; Enqi Zhang; Shuming Lin; Zihong Li; Jing Tian; Zijie Wei; Zihan Liu; Mengyao Liang; Runqian Jiang; et al. (Marine Pollution Bulletin, 2026)

Phosphorus availability overrides evolutionary adaptation to warming and high carbon dioxide in shaping diatom physiology and lipid metabolism - Mengcheng Ye; Peixuan Liu; Jiamin Lin; Siyu Luan; Meimei He; Tian Shen; Zexu Li; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; et al. (Limnology and Oceanography, 2026)
Rising ocean temperatures and CO 2 concentrations are reshaping phytoplankton physiology, yet how long‐term adaptation to these stressors interacts with nutrient limitation remains poorly understood. Phosphorus (P) frequently limits phytoplankton growth in coastal and stratified oceans, but it remains unclear whether adaptation to warming and elevated CO 2 modifies responses to P limitation and whether such adaptive advantages can be realized under nutrient stress. Here, we combined multi‐year experimental evolution of the model diatom Phaeodactylum tricornutum under warming, elevated CO 2 , and their combination with short‐term assays across a phosphorus gradient to examine how evolutionary history influences responses to P availability. Across all adaptation regimes, P availability overwhelmingly governed growth, photosynthetic performance, and lipidome structure. Long‐term adaptation increased maximum growth rate and phosphate affinity, but these advantages were largely suppressed under P limitation. Lipidomic analyses revealed extensive P‐driven membrane remodeling, characterized by declines in phospholipids and increases in glycolipids and neutral lipids. While lipid‐class remodeling remained highly conserved across adaptation regimes, structural lipid traits responded differently depending on both evolutionary history and phosphorus status. Under P‐replete conditions, warming and elevated CO 2 primarily promoted fatty‐acid elongation, whereas under P limitation they increased fatty‐acid desaturation. These results demonstrate that nutrient regimes constrain evolutionary responses to warming and elevated CO 2 , highlighting phosphorus as a key determinant of diatom resilience in future oceans. Increasing nutrient limitation in future oceans may therefore restrict the extent to which phytoplankton populations can realize adaptive advantages under climate change, with implications for marine productivity and biogeochemical cycling.

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

Rapid evolution of marine phytoplankton under global change: mechanisms, constraints, and ecological consequences - Siyu Luan; Peixuan Liu; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; Tian Shen; Meimei He; Zexu Li; Jianrong Xia; Peng Jin (Marine Environmental Research, 2026)

Development and Validation of a Multienzyme Isothermal Rapid Amplification Combined with Lateral-Flow Dipstick (MIRA-LFD) Assay for Trypanosoma Strains Circulating in Large Yellow Croaker (Larimichthys crocea) - You Zuo; Bichai Liao; Luoxuan Lin; Tong Wu; Jiahao Yuan; Qianxi Xue; Haiyun Wei; Shuming Liu; Guangliang Huang; Xinhua Chen; Pan Qin (Fishes, 2026)
Trypanosomiasis, caused by flagellated protozoa of the genus Trypanosoma, has recently emerged as a major threat to aquaculture in China, particularly in farmed large yellow croaker (Larimichthys crocea). Outbreaks lead to high mortality rates and severe economic losses. Conventional diagnostic tools, such as blood-smear microscopy and molecular assays including polymerase chain reaction or quantitative polymerase chain reaction (qPCR), are often limited by low sensitivity during early infection or by their dependence on sophisticated instruments and trained personnel, restricting their utility in field conditions. To address these challenges, a multienzyme isothermal rapid amplification (MIRA) assay coupled with a lateral-flow dipstick (LFD) was developed for the rapid detection of trypanosoma strains circulating in L. crocea targeting the 18S ribosomal ribonucleic acid gene. After optimizing primer-probe sets, the assay performance was evaluated using plasmid standards and a panel of common aquaculture pathogens. The MRA-LFD assay consistently detected plasmid DNA at concentrations as low as 0.01 fg/µL (≈2.1 copies/µL) and demonstrated no cross-reactivity with other pathogens. Using clinical DNA samples positive for Trypanosoma, the detection limit was 100 fg µL−1. Validation with 150 tissue samples from fish with and without clinical symptoms demonstrated high diagnostic consistency (94%) with qPCR results, confirming the reliability of the assay. This MIRA-LFD platform provides a sensitive, specific and portable diagnostic tool for early detection of Trypanosoma infections in large yellow croaker, offering valuable support for surveillance and disease management in aquaculture.

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Comparative study on feeding habits, gonadal development and muscle nutritional value in triploid hybrids derived from blunt snout bream (Megalobrama amblycephala, ♀) × topmouth culter (Culter alburnus, ♂) - Guang-hai Dong; Zheng-nan Liu; Song-lin Chen; Yahui Feng; Jie Chen; Guodong Zheng; Shuming Zou (Aquaculture International, 2025)

A comparative metabolomics study on two fresh edible lilies for vegetable: Lilium brownii var. viridulum and Lilium davidii var. unicolor - Lu Mi; Kewen Wang; Zhilin Gan; Yuhong Lin; Xue Wang; Shuming Yang; Zhenzhen Xu (Food Bioscience, 2024)

Effect of regulating dissolved oxygen concentration in pulp with aerated gas on pyrite flotation - Ximei Luo; Wen Yang; Shuming Wen; Qiqiang Lin; Dayong Wei; Chao Li; Ying Zhang; Zhenguo Song; Yunfan Wang (Minerals Engineering, 2023)

Interaction between STK33 and autophagy promoted renal cell carcinoma metastasis by regulating mTOR/ULK1 signaling pathway - Xiaomei Li; Min Lin; Min Liu; Hong Ye; Shuming Qin (Molecular Biology Reports, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Leucine attenuates muscle atrophy and autophagosome formation by activating PI3K/AKT/mTOR signaling pathway in rotator cuff tears - Rongzong Zheng; Shuming Huang; Junkun Zhu; Wei Lin; Huan Xu; Xiang Zheng (Cell and Tissue Research, 2019)

Study on the nutritional value and ruminal degradation characteristics of fermented waste vinegar residue by N. sitophila - Ci Liu; Lin Zhang; Jiye Yang; Wenjia Zhang; Qianqian Wang; Jianxin Zhang; Jiaying Xin; Shuming Chen (Tropical Animal Health and Production, 2019)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Modulation of prostate cancer cell gene expression by cell-to-cell contact with bone marrow stromal cells or osteoblasts - Shuming Zhang; Jun Wang; Mehmet A. Bilen; Sue-Hwa Lin; Samuel I. Stupp; Robert L. Satcher (Clinical & Experimental Metastasis, 2009)

Cloning and characterization of a novel Δ12-fatty acid desaturase gene from the tree Sapium sebiferum - Bei Niu; Huaxun Ye; Ying Xu; Shenghua Wang; Peng Chen; Shuming Peng; Yangchao Ou; Lin Tang; Fang Chen (Biotechnology Letters, 2007)

Determination of Organophosphorus Pesticides and Related Compounds in Water Samples by Membrane Extraction and Gas Chromatography - Pengxiang Xu; Dongxing Yuan; Shuming Zhong; Qingmei Lin (Environmental Monitoring and Assessment, 2003)